2017
DOI: 10.1007/s00347-017-0449-3
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich von Trabekulektomie und Kanaloplastik

Abstract: Both procedures provide a safe and efficient IOP reduction. Trabeculectomy is able to achieve an even better IOP reduction without application of additional postoperative medication. Canaloplasty requires shorter inpatient stay, less frequent postoperative checkups and interventions as well as a less severe spectrum of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Throughout the follow-up period, every second modified canaloplasty case needed supplemental AGM, whereas 89.3% of trabeculectomy cases did not, and the number of medications was significantly lower after trabeculectomy than after modified canaloplasty. The same trend (either significant or not) was visible in all previous comparative studies [ 12 , 16 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 ] except the study of Brüggemann et al, where none of the canaloplasty cases and three of the trabeculectomy cases were on topical AGM [ 21 ]. The meta-analysis by Zhang et al found that AGM was slightly more reduced after trabeculectomy than after canaloplasty by 0.37 medicaments ( p = 0.11) [ 23 ]; the two other meta-analyses by Liu et al and Rulli et al, however, they did not analyze the number or reduction of AGM [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Throughout the follow-up period, every second modified canaloplasty case needed supplemental AGM, whereas 89.3% of trabeculectomy cases did not, and the number of medications was significantly lower after trabeculectomy than after modified canaloplasty. The same trend (either significant or not) was visible in all previous comparative studies [ 12 , 16 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 ] except the study of Brüggemann et al, where none of the canaloplasty cases and three of the trabeculectomy cases were on topical AGM [ 21 ]. The meta-analysis by Zhang et al found that AGM was slightly more reduced after trabeculectomy than after canaloplasty by 0.37 medicaments ( p = 0.11) [ 23 ]; the two other meta-analyses by Liu et al and Rulli et al, however, they did not analyze the number or reduction of AGM [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 74%
“…Contrarily, no reports of endophthalmitis following canaloplasty have been reported yet, however, the presence of a filtering bleb carrying the danger for blebitis has been described in up to 10% of cases after canaloplasty [ 28 ]. Compared to canaloplasty, a higher occurrence of postoperative hypotony after trabeculectomy has been reported with a proportion of 16–37% [ 20 , 26 ]. Zhang et al found 9-times higher odds for hyphema ( p < 0.001) in the canaloplasty groups, whereas the odds were a third ( p = 0.01) for hypotony and a quarter ( p = 0.03) for choroidal effusion/detachment in the canaloplasty groups compared to trabeculectomy groups.…”
Section: Discussionmentioning
confidence: 99%
“…Author/year Egrilmez 2004 [6] El-Saied 2014 [7] Hong 2012 [8] Jankowska 2018 [9] Taruttis 2018 [10] Research El-Saied 2014 [7] 2 0 1 3…”
Section: Table 1 Baseline Characteristics Of Included Studiesmentioning
confidence: 99%